Pengaruh Sistem Informasi Akuntansi Terhadap Kelebihan Bayar Pajak - Ririn Miptha Nuryana; Decky Hendarsyah (Jurnal Ilmiah Akuntansi Kesatuan, 2021)
The awareness of taxpayers in paying taxes is very necessary because development in Indonesia requires very large funds, one source of government funds is revenue from the taxation sector so that state revenue can be met and development can continue. This study aims to complement the shortcomings of existing studies and to analyze the effect of the accounting information system (AIS) on tax overpayment (TOP) at the regional financial and asset management agency (RFAMA) of Bengkalis Regency. This study uses a quantitative descriptive method with primary and secondary data sources. The total population at the office of the RFAMA of Bengkalis Regency was 260 people. The sampling technique used purposive sampling, to obtain a sample of 30 people. Data collection techniques using questionnaires, interviews, documentation and literature study. Data analysis using are simple linear regression method, hypothesis testing and coefficient of determination. The results of this study indicate that the AIS have a significant effect on TOP at the RFAMA of Bengkalis Regency. This study can contribute to the office of the RFAMA of Bengkalis Regency in implementing an AIS and minimizing the occurrence of TOP.